Health-Related Quality of Life in Sarcoidosis - Obi, Ogugua Ndili (Seminars in Respiratory and Critical Care Medicine, 2020)
Health-related quality of life (HRQoL) describes an individual's perception of the impact of health, disease, and treatment on their quality of life (QoL). It is a reflection of how the manifestation of an illness and its treatment is personally experienced. Assessing HRQoL is particularly important in sarcoidosis because the attributable disease mortality is relatively low, and one of the major reasons for initiating treatment is to improve quality of life. HRQoL has been assessed in sarcoidosis using various generic and sarcoid-specific patient-reported outcome measures (PROMs). It is important that both the direct and indirect effects of the disease, as well as potential toxicities of therapy, are captured in the various PROMs used to assess HRQoL in sarcoidosis. This article provides a general overview of HRQoL in patients with sarcoidosis. It describes the various PROMs used to assess HRQoL in sarcoidosis and addresses the various factors that influence HRQoL in sarcoidosis. Specific attention is paid to fatigue, small fiber neuropathy, corticosteroid therapy, and other disease-specific factors that affect HRQoL in sarcoidosis. It also provides an insight into interventions that have been associated with improved HRQoL in sarcoidosis and offers suggestions for future research in this important area.
Keywords: sarcoidosis; health-related quality of life; fatigue; dyspnea; small fiber neuropathy; patient-reported outcome measures; depression; supervised exercise training program